Cumulative radiation exposure and associated cancer risk estimates for scoliosis patients: Impact of repetitive full spine radiography. Issue 3 (March 2016) - Law, Martin; Ma, Wang-Kei; Lau, Damian; Chan, Eva; Yip, Lawrance; Lam, Wendy
Abstract: Objective: To quantitatively evaluate the cumulative effective dose and associated cancer risk for scoliotic patients undergoing repetitive full spine radiography during their diagnosis and follow up periods. Methods: Organ absorbed doses of full spine exposed scoliotic patients at different age were computer simulated with the use of PCXMC software. Gender specific effective dose was then calculated with the ICRP-103 approach. Values of lifetime attributable cancer risk for patients exposed at different age were calculated for both patient genders and for Asian and Western population. Mathematical fitting for effective dose and for lifetime attributable cancer risk, as function of exposed age, was analytically obtained to quantitatively estimate patient cumulated effective dose and cancer risk. Results: The cumulative effective dose of full spine radiography with posteroanterior and lateral projection for patients exposed annually at age between 5 and 30 years using digital radiography system was calculated as 15 mSv. The corresponding cumulative lifetime attributable cancer risk for Asian and Western population was calculated as 0.08–0.17%. Female scoliotic patients would be at a statistically significant higher cumulated cancer risk than male patients under the same full spine radiography protocol. Conclusion: We demonstrate the use of computer simulation and analytic formula to quantitatively obtain the cumulated effective dose and cancer risk at any age of exposure, both of which are valuable information to medical personnel and patients' parents concern about radiation safety in repetitive full spine radiography.